2021
DOI: 10.18844/cjes.v16i5.6331
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of community-based education management: A case study of Islamic boarding schools in Bengkulu City, Indonesia

Abstract: The purpose of this study is to reveal the objective conditions and characteristics of Islamic boarding school management as a model of community-based education in Bengkulu City. This study uses a qualitative approach, the method used is a single instrumental case study. The data collection process used (1) in-depth interviews, (2) participatory observation, and (3) documentation study. The data analysis technique is domain analysis by focusing on terms, semantic relationships, and the phrases they cover. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The stages passed will ultimately be useful when involved in the community and the task of pesantren (through students), one of which is to grow public awareness of the religious understanding that is their responsibility. (Zulkarnain &;Zubaedi, 2021)…”
Section: Responsibilitymentioning
confidence: 99%
“…The stages passed will ultimately be useful when involved in the community and the task of pesantren (through students), one of which is to grow public awareness of the religious understanding that is their responsibility. (Zulkarnain &;Zubaedi, 2021)…”
Section: Responsibilitymentioning
confidence: 99%
“…Management etymologically comes from the English language, namely from the word "to manage" with the equation "to hand" means to take care of "to control" means to check, "to guide" to lead. So it can be concluded that management means taking care of, implementing, organizing, and managing (Zulkarnain, 2021). Thus the word management in translation Indonesian means leadership, how to lead, manage, arrangement, mastery and others (Prayogi, 2021).…”
Section: Curriculum Management Conceptsmentioning
confidence: 99%
“…In terms of Islamic psychological values, there should be a multicultural education model. In this case, multicultural Islamic education also needs to be touched and entered into by the values of Islamic psychology (Rahmat & Yahya, 2022), because education will always intersect with personality, both educators and students (Zulkarnain & Zubaedi, 2021). Hasbullah (2016) said that Islamic education should bring calm, comfort, and peace to the world of education.…”
Section: Introductionmentioning
confidence: 99%